Introduction - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Energy-efficient office renovation is obviously required for the reasons mentioned in the previous section, and there is a great growth of energy renovation projects in practice. However, does a high energy performance office provide a comfortable working environment to its users? One of the reasons of office existence is to provide comfortable and healthy indoor environments (Ornetzeder et al., 2016). According to Klepeis et al. (2001), people spend over 80% of their time in enclosed spaces. Moreover, good indoor environments can lead to an increase of occupants’ productivity (Al-Horr et al., 2016). For these reasons, planning healthy and comfortable work environment can be as important as reducing energy use. The question is, how can we design healthy and comfortable work environments, with which the users are satisfied? The starting point to answer this question is to include building users’ requirements and satisfaction in workspaces in energy renovation schemes. A concern is that conventional renovation principles are mainly physical- and technical-oriented, whereas it does not focus on enhancing user satisfaction in the work environment. Moreover, as long as the renovated building does not offer sufficient quality or satisfaction, there will be less demand for renovated office buildings. When energy efficiency is considered as the only advantage of office renovation, it is difficult to convince developers, building owners, and investors that renovation is useful. From a managerial perspective, achieving better employee’s satisfaction should be a focal point to strengthen the market values of renovated offices, thereby achieving a higher demand from the market, preventing environmental degradation or vacancy of existing buildings. Therefore, office renovation also has to provide a high-level of comfortable work environment for the users’ well-being and satisfaction beside maximising energy reduction goals. Therefore, there is a significant need to investigate how to define the users’ satisfaction to contribute to better office renovations. The relationship between indoor climate and users’ physical health has been explored in extensive research (Al Horr et al., 2016; Bluyssen et al., 2016; Leder et al., 2016; Mandin et al., 2017). Followed by these studies, the framework of international green building rating systems such as Leadership in Energy and Environmental Design (LEED) and Building Research Establishment Environmental Assessment Method (BREEAM) include a category of social sustainability as a means of providing a healthy and comfortable environment to users for both new and renovated buildings (Sarkis et al., 2012; Zuo & Zhao, 2014). Although international green building rating systems address the significance of including user perspectives, there is a lack of guidelines and information that focus on user satisfaction in building renovation. Especially, the relationship between design factors and user satisfaction has rarely been investigated due to several reasons; user satisfaction is a subjective topic; design factors are closely related to energy efficiency and aesthetic aspects rather than user satisfaction. Therefore, the main problem is that in spite of the development of various renovation techniques, there is still a lack of renovation design principles considering user preferences and user satisfaction due to the indirect relationship with energy use. In any renovation project, the initiative is the most significant phase to ensure proper decisions and to optimise overall renovation values and results, that should be considered in the early renovation design stage. Jensen and Maslesa (2015) stated that the main barriers include lack of standard principles and a lacking overview of potential values in the initiative phase. To summarise all these aspects, it is required to develop an overview of potential values and standard design principles that not only focus on energy efficiency but also on the building users for office renovations.